The effect of peer support in adults with insulin pump-treated type 1 diabetes: a pilot study of a flexible and participatory intervention - Joensen LE; Meldgaard Andersen M; Jensen S; Nørgaard K; Willaing I (Patient Preference and Adherence, 2017)
Lene Eide Joensen,1 Merete Meldgaard Andersen,2 Sabrina Jensen,1 Kirsten Nørgaard,2 Ingrid Willaing1 1Diabetes Management Research, Steno Diabetes Center Copenhagen, Gentofte, 2Department of Endocrinology, Hvidovre Hospital, Hvidovre, Denmark Aim: The aim of this study was to explore the effects of a flexible and participatory peer support intervention in a clinical setting for adults with type 1 diabetes treated with an insulin pump, focusing on enhancing diabetes-specific social capital. The key questions were as follows: 1) what effects are appropriate to expect, according to participants? and 2) to what extent did these effects occur? Methods: Two peer support intervention programs were conducted in a diabetes specialist clinic (N=30). A participatory and adaptable approach allowed flexibility in the content of peer support meetings, which were facilitated by a diabetes nurse. Individual interviews explored participants’ perception of effects of the intervention. Interview data were analyzed qualitatively. Participants (n=27) completed a baseline and postintervention questionnaire that included items assessing diabetes empowerment, diabetes distress, diabetes-specific social support, and diabetes loneliness. HbA1c levels were compared before and after the intervention. Results: Participants experienced enhanced diabetes-specific social capital, diabetes motivation, awareness of personal diabetes practices, and serenity and openness in life with diabetes. They also became more aware of treatment and support possibilities. Negative effects included feeling sad or upset after the meetings or feeling different than and not as well-controlled as other participants. Quantitative analyses showed enhanced social support, decreased eating distress and trends toward enhanced diabetes empowerment, decreased diabetes loneliness, and decreased diabetes distress (powerlessness). We found fewer positive and/or negative outcomes among participants who felt no need for peer support or felt that the group was not a unit or that important issues were not addressed. Conclusion: The study indicated that flexible and participatory peer support can strengthen diabetes-specific social capital and improve participants’ well-being and diabetes empowerment. Awareness of participants’ incentives for attending peer support, as well as the risk of people feeling isolated within peer support groups, is essential to creating effective diabetes-specific social support. Keywords: type 1 diabetes mellitus, insulin pump therapy, psychosocial support, psychological well-being, empowerment, exploratory research